Numerical modeling of viscoelastic behavior of filled rubber vulcanizates - Solodko, Vladislav Nikolaevich; Svistkov, Aleksandr Lvovich; Pelevin, Aleksandr Gennadievich (Computational Continuum Mechanics, 2014)
The paper focuses on the numerical implementation of constitutive relations of a continuum viscoelastic model, which describes the behavior of filled rubber vulcanizates under finite deformations. In the model, the additive decomposition of the strain rate tensor and the concept of macro and structural levels of deformation are used. The equilibrium hyperelastic behavior of a polymer binder is represented by relations that are based on the generalized tube model. Rheological properties are represented as differential relations. Various types of a term in the expression for free energy potential responsible for relaxation properties are tested. The viscous flow coefficient is analyzed as a function of continuum parameters and internal tensor variables. Simulation results are compared with the experimental data for filled rubber vulcanizates under uniaxial cyclic loading.